Sero-epidemiology as a tool to screen populations for exposure to Mycobacterium ulcerans. - Dorothy Yeboah-Manu; Katharina Röltgen; William Opare; Kobina Asan-Ampah; Kwabena Quenin-Fosu; Adwoa Asante-Poku; Edwin Ampadu; Janet Fyfe; Kwadwo Koram; Collins Ahorlu; Gerd Pluschke (Public Library of Science (PLoS), 2012)
BACKGROUND: Previous analyses of sera from a limited number of Ghanaian Buruli ulcer (BU) patients, their household contacts, individuals living in BU non-endemic regions as well as European controls have indicated that antibody responses to the M. ulcerans 18 kDa small heat shock protein (shsp) reflect exposure to this pathogen. Here, we have investigated to what extent inhabitants of regions in Ghana regarded as non-endemic for BU develop anti-18 kDa shsp antibody titers. METHODOLOGY/PRINCIPAL FINDINGS: For this purpose we determined anti-18 kDa shsp IgG titers in sera collected from healthy inhabitants of the BU endemic Densu River Valley and the Volta Region, which was so far regarded as BU non-endemic. Significantly more sera from the Densu River Valley contained anti-18 kDa shsp IgG (32% versus 12%, respectively). However, some sera from the Volta Region also showed high titers. When interviewing these sero-responders, it was revealed that the person with the highest titer had a chronic wound, which was clinically diagnosed and laboratory reconfirmed as active BU. After identification of this BU index case, further BU cases were clinically diagnosed by the Volta Region local health authorities and laboratory reconfirmed. Interestingly, there was neither a difference in sero-prevalence nor in IS2404 PCR positivity of environmental samples between BU endemic and non-endemic communities located in the Densu River Valley. CONCLUSIONS: These data indicate that the intensity of exposure to M. ulcerans in endemic and non-endemic communities along the Densu River is comparable and that currently unknown host and/or pathogen factors may determine how frequently exposure is leading to clinical disease. While even high serum titers of anti-18 kDa shsp IgG do not indicate active disease, sero-epidemiological studies can be used to identify new BU endemic areas.